Evolution and critique of buffer stocking policy of India - Shweta Saini; Marta Kozicka (Indian Council for Research on International Economic Relations (ICRIER), 2014)
India's economic standing and its policy landscape have come a long way since the 1943 Bengal famine. History saw buffer stocking of food grains as a famine-combating tool. Today, apart from serving as an effective hedge in times of famines, such grain stocks are a conduit deployed by the government to foster the country's agriculture development and food security. The buffer stocking policy of food grains has become the one tool with the government used to fulfil the interlinked objectives of supporting food-producers and food-consumers, and of ensuring food availability at the national level. The policy of widespread government intervention in the food management of the country has been successful in many ways. From a food-scarce, food-importing country, India has emerged as a grain-surplus and a net grain-exporting country. The production base is strong and growing. Food security, in terms of ample grain supplies, has been attained at the national level. However, an evaluation of the country's buffer stock policy reveals gaps and inefficiencies. Large quantities of food grains have accumulated in the godowns of the Food Corporation of India (FCI) and its nominated state agencies, raising questions about the economic efficiency of the entire operation. At the same time, there is high incidence of malnutrition and rising food grain prices across the country. The level of government intervention in grain markets is straining government finances because of the increasing burden of food subsidy. There are increasing concerns regarding the imbalances being created in the national production basket, of alienation of market forces and its players, of quality of grain, and the sustainability and relevance of such operations.
Keywords: Q18; N50; H44; E61; H57; I38; O13; Q13; 330; Buffer Stocks; Indian Agriculture; Price Stabilisation; Food Security; Food Policies